Accompaniment in Determining the Cost of Goods Sold (COGS) And Product Branding at D'zegerrr As a Micro Small and Medium Enterprise - Sari, Rika Puspita; Shanty, Ratna Nur Tiara; Prayudanti, Adhania Andika (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This study aims to assist the MSME